Cellular biology of bone resorption. - Zaidi, M; Alam, A; Shankar, V; Bax, B; Bax, C; Moonga, B; Bevis, P; Stevens, C; Blake, DR; Pazianas, M (1993)
Past knowledge and the recent developments on the formation, activation and mode of action of osteoclasts, with particular reference to the regulation of each individual step, have been reviewed. The following conclusions of consensus have emerged. 1. The resorption of bone is the result of successive steps that can be regulated individually. 2. Osteoclast progenitors are formed in bone marrow. This is followed by their vascular dissemination and the generation of resting preosteoclasts and osteoclasts in bone. 3. The exact pathways of differentiation of the osteoclast progenators to mature osteoclasts are debatable, but there is clear evidence that stromal cells support osteoclast generation. 4. Osteoclasts are activated following contact with mineralized bone. This appears to be controlled by osteoblasts that expose mineral to osteoclasts and/or release a factor that activates these cells. 5. Activated osteoclasts dissolve the bone mineral and digest the organic matter of bone by the action of agents secreted in the segregated microcompartments underlying their ruffled borders. The mineral is solubilized by protons generated from CO2 by carbonic anhydrase and secreted by an ATP-driven vacuolar H(+)-K(+)-ATPase located at the ruffled border. The organic matrix of the bone is removed by acid proteinases, particularly cysteine-proteinases that are secreted together with other lysosomal enzymes in the acid environment of the resorption zone. 6. Osteoclastic bone resorption is directly regulated by a polypeptide hormone, calcitonin (CT), and locally, by ionized calcium (Ca2+) generated as a result of osteoclastic bone resorption. 7. There is new evidence that osteoclast activity may also be influenced by the endothelial cells via generation of products including PG, NO and endothelin.